Denial of secularism, authoritarian thinking and decharacterization of public school in Brazil - Pacheco, Luiz André; Derisso, José Luis (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
The distortion of the public school in relation to your order to socialize historically accumuled and developed knowledge in the contexto of science, philosophy and art occurs by various means and devices. In this article we identified four of them, namely:  the Religious Education, that was established in 1931, a clear denial of the secular character of the school and the State; the combating gender approach on the grounds of protection of the family; the Program Escola Sem Partido by means of projects from the Senate even the municipalities aims to deploy the censorship to reflections and critical approaches about society into the schools; and the High School Reform which deepens the technical and pragmatic orientation of school education while reducing the workload of some subjects and excludes others. Such a scenario favors the development of uncritical adaptation form of education for children and young people to social and economic order of capitalism and of moral which best represents itself, abridging the flourishing of critic pedagogies not hegemonics.